2015
DOI: 10.1155/2015/686259
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dentine on the pH of Calcium Hydroxide, Chlorhexidine Gel, and Experimental Bioactive Glass‐Based Root Canal Medicament

Abstract: Objectives. To evaluate the influence of dentine on the pH of different medications in standardized simulated canals. Materials and Methods. Forty resin blocks were divided into groups with and without dentine powder, as follows: 2% chlorhexidine gel; 2% chlorhexidine gel associated with calcium hydroxide PA; calcium hydroxide PA delivered in propylene glycol 600; and NPG delivered in distilled water. The dentine powder was obtained from the root dentine of bovine teeth and added to the medications. The simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…[ 28 ] Another possible reason is the buffering capacity of dentin which brings down the alkalinity of calcium hydroxide rendering it less effective. [ 29 ] These cases were further treated with triple antibiotic paste.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] Another possible reason is the buffering capacity of dentin which brings down the alkalinity of calcium hydroxide rendering it less effective. [ 29 ] These cases were further treated with triple antibiotic paste.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental glass there was an interruption of release on the 14th day, but release began again on the 21st day and its levels were equal to the release at 7 days. A possible explanation for this is that the chemical stability of phosphate glasses increases when niobium is added (24,25), thus leading to a slightly slower release of ions. A higher level of sodium ion release was observed for the groups CHX and GB, with a statistically higher immediate level of release for the glass than for all the other groups.…”
Section: Ions Release and Ph Of Endodontic Medicamentsmentioning
confidence: 99%
“…Such results concur with those of other studies that found pH values between 9 and 12. 32,33,34,35 However, Carvalho et al 36 observed that when CHX was used as the vehicle, the peak pH was achieved immediately after preparation of the medication (pH = 9); after 7 days, the pH was neutral. These authors have questioned the efficacy of the combination of CHX and CH.…”
Section: Discussionmentioning
confidence: 99%